Hand-to-surface bacterial transfer and healthcare-associated infections prevention: a pilot study on skin microbiome in a molecular biology laboratory - Delicati, Arianna; Marcante, Beatrice; Catelan, Dolores; Biggeri, Annibale; Caenazzo, Luciana; Tozzo, Pamela (Frontiers in Medicine, 2025)
BackgroundHealthcare-associated infections (HAIs) are a major global public health problem, contributing significantly to patient morbidity and mortality. This study analyses differences in type and amounts of bacteria transferred from volunteers’ dominant palm to two healthcare-relevant surfaces (glass and laminate table), both before and after hand washing with water and antibacterial soap. The aim was to understand hand-to-surface microbial contamination and support the development of HAI prevention strategies.MethodsMicrobial DNA was extracted and sequenced to identify bacteria species. Taxonomic and statistical analyses were performed to evaluate bacterial diversity and abundance across the experimental groups.ResultsThe results confirmed greater bacteria abundance and species richness on palm compared to surfaces, with a significant reduction after hand washing, especially on glass. Taxa analysis highlighted the increased persistence of Gram-negative HAIs-related bacteria on laminate surface, while Gram-positive opportunistic bacteria were more abundant on palms and glass surface. Beta diversity confirmed significant differences in microbial composition between the groups, highlighting the importance of bacteria-surface characteristics in designing preventive measures.ConclusionDespite some limitations, our study emphasizes the importance of microbiological surveillance for all opportunistic bacteria with pathogenic potential. These findings can contribute to more effective guidelines for surface disinfection and hand washing, key elements in preventing HAIs.